Short and medium-term effects of secundum atrial septal defect percutaneous closure using the Amplatzer Septal Occluder in the elderly. Issue 4 (2017) - Broadley, Andrew; Gogola, Laisha; , Carl Roobottom; Ring, Nicholas; Marshall, Andrew J
No abstract available